The image of the late-Francoist Spain in the films of Manolo Escobar [La imagen de la España tardofranquista en las películas de Manolo Escobar] (2013)
As part of a research project that examines the 200 most popular films during the Late-Francoist Spain, this article offers a qualitative analysis of the ten films that were produced from 1966 and 1975 and were starred by the actor and singer Manolo Escobar, who was the most profitable artist of that time and delivered the most explicit messages. The analysis focuses on the values, ideas and beliefs transmitted by these films, which were presented to the public as just entertainment but were in essence ideological vehicles. The male dominance, the subservience of women, the exploitation of other Celtiberian issues that had relevance at that time, the glorification of the all things Spanish when in presence of foreignness are some of the characteristic features of these musical comedies whose happy endings suggested that success was within the reach of anyone who complied with the prevailing codes of conduct of the late-Francoist Spain.